2018
DOI: 10.3390/pharmaceutics10030086
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability Enhancement of Poorly Water-Soluble Drugs via Nanocomposites: Formulation–Processing Aspects and Challenges

Abstract: Drug nanoparticles embedded in a dispersant matrix as a secondary phase, i.e., drug-laden nanocomposites, offer a versatile delivery platform for enhancing the dissolution rate and bioavailability of poorly water-soluble drugs. Drug nanoparticles are prepared by top-down, bottom-up, or combinative approaches in the form of nanosuspensions, which are subsequently dried to prepare drug-laden nanocomposites. In this comprehensive review paper, the term “nanocomposites” is used in a broad context to cover drug nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(100 citation statements)
references
References 227 publications
(478 reference statements)
1
95
0
1
Order By: Relevance
“…According to previous reports, Cremophor EL ® , also known as Kolliphor EL (HLB value = 13.5), has often been investigated owing to its better emulsifying capacity than the Tween series [44]. Cremophor EL ® demonstrates enhanced permeability and bioavailability, although it is a nonionic surfactant [45]. Based on our data, Cremophor EL ® showed a higher solubility than Labrasol and Tween 80.…”
Section: Discussionsupporting
confidence: 54%
“…According to previous reports, Cremophor EL ® , also known as Kolliphor EL (HLB value = 13.5), has often been investigated owing to its better emulsifying capacity than the Tween series [44]. Cremophor EL ® demonstrates enhanced permeability and bioavailability, although it is a nonionic surfactant [45]. Based on our data, Cremophor EL ® showed a higher solubility than Labrasol and Tween 80.…”
Section: Discussionsupporting
confidence: 54%
“…APIs released from ASDs were determined via a Distek 2100C dissolution tester (North Brunswick, NJ) using the United States Pharmacopeia II paddle method. The use of the DI water was based on previous studies [47][48][49] that indicated improved size discrimination. Furthermore, no surfactant was used because for crystalline GF, the use of the surfactants prevents from discerning the effect of particle size on the dissolution behavior of the drug.…”
Section: Dissolution Testmentioning
confidence: 99%
“…The DI water was used based on previous publications identifying that it allows for better discernment of the particle size effect of crystalline GF. [47][48][49] The effect of particle size and recrystallization inhibitor amount on the dissolution rate and the recrystallization rate in solution of ASDs were examined. Finally, dissolution mechanisms and recrystallization rate kinetics were also discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the term “nanocomposite” more specifically refers to nanoparticles (nanosuspensions) subjected to a drying process to intentionally recover nanoaggregates that are able to redisperse in a liquid (reversible or irreversible aggregates) [ 52 ].…”
Section: Introductionmentioning
confidence: 99%